BAKAT ANAK DALAM PERSPEKTIK PSIKOLOGI - Umi Musya'adah (Jurnal Keislaman, 2021)
Talent is a capacity or potential that is influenced by experience orlearning, talent is related to the possibility of mastering a pattern of behavior in certainaspects of life. In my opinion talent is innate which is the potential to actualize himself as aservant (abid) who serves Allah and is the potential to actualize himself as (Khalifatullah)on earth, therefore talent must always be developed through exercises, so that talent will bewill help to become a responsible caliph. There is a close relationship between intelligenceand talent of children. This is indicated by the understanding of the child's own talentwhich means great potential in a type of intelligence. While intelligence itself is dividedinto several aspects, namely logical and mathematical intelligence, language intelligence,visual-spatial intelligence or imagination, kinesthetic or physical intelligence, musicalintelligence, interpersonal or social intelligence, intrapersonal intelligence, naturalistintelligence, spiritual intelligence, and financial intelligence. . This means that a person'stalent can lead to one of these intelligences.